(untitled) (Proceedings of the International Conference on Future of Education, 2018)
Globalization has various interpretations and ithas been the rationale behind internationalizinghighereducation.Internationalizationofhighereducationstartedinthepastthreedecadesglobally.TheterminternationalizationofhighereducationhasbeenwidelydiscussedinMalaysiainthepasttwodecades. The survival and acceptance of Higher Learning Institution (HLI)s are highly dependent on how much elements of the internationalization are incorporated into these institutions. EventhoughMalaysianHLIshavespearheadedthiseffortadecadeago,itseemstobeagoalfarreachingforsomeHLIs.DespiteinternationalizationeffortshasbeentakenbyMinistryofHigherEducationMalaysia(MOHE),thereisnosignificantandconclusivestudyonhowHLIsinMalaysiaaresuccessfulinmeetingtheglobalneedsandrequirements and whatare thebarriers thatprohibiting Malaysian HLIsin achievingits internationalizationgoals. It is important to pay close attention to the development of Malaysian Higher Education System and the barriers towards internationalisation to be sustainable in global environment. This conceptual paper examines on the important factors in sustainability of higher education in Malaysia and proposes conceptual framework to study the important factors in pursuit of global mindedness among Malaysian HLIs.